2006
DOI: 10.1091/mbc.e05-11-1010
|View full text |Cite
|
Sign up to set email alerts
|

The Kinesin KIF1C and Microtubule Plus Ends Regulate Podosome Dynamics in Macrophages

Abstract: Microtubules are important for the turnover of podosomes, dynamic, actin-rich adhesions implicated in migration and invasion of monocytic cells. The molecular basis for this functional dependency, however, remained unclear. Here, we show that contact by microtubule plus ends critically influences the cellular fate of podosomes in primary human macrophages. In particular, we identify the kinesin KIF1C, a member of the Kinesin-3 family, as a plus-end-enriched motor that targets regions of podosome turnover. Expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
151
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(167 citation statements)
references
References 47 publications
14
151
2
Order By: Relevance
“…Because it has been suggested that the degradation activity is directly correlated to the half-life of the structures (Linder, 2007), the observed increase of these two parameters might in fact reflect a reduction in podosome turnover in p190A-KD cells. The microtubule cytoskeleton was shown to be involved in podosome dynamics in macrophages (Kopp et al, 2006); however, we were not able to detect any alteration in the pattern of α-tubulin in these modified cells. Thus, our data suggest that, even if p190A and p190B proteins share a high degree of homology and are involved in similar signalling cascades, they might control actin-cytoskeleton-based processes through distinct mechanisms.…”
Section: Discussioncontrasting
confidence: 88%
“…Because it has been suggested that the degradation activity is directly correlated to the half-life of the structures (Linder, 2007), the observed increase of these two parameters might in fact reflect a reduction in podosome turnover in p190A-KD cells. The microtubule cytoskeleton was shown to be involved in podosome dynamics in macrophages (Kopp et al, 2006); however, we were not able to detect any alteration in the pattern of α-tubulin in these modified cells. Thus, our data suggest that, even if p190A and p190B proteins share a high degree of homology and are involved in similar signalling cascades, they might control actin-cytoskeleton-based processes through distinct mechanisms.…”
Section: Discussioncontrasting
confidence: 88%
“…Nevertheless, intact microtubules are required for the function of other invadosomes, such as podosomes of monocytes, macrophages, and osteoclasts 1,112,113 . In breast cancer cells, intact microtubules are not necessary for invadopodia formation, 114,115 but their destruction affects invadopodia elongation and maturation.…”
Section: The Invasive Domainmentioning
confidence: 99%
“…Finally, microtubules and microtubulebased motor proteins such as the kinesin KIF1C also play a role in the fission (the formation of new podosomes by splitting off from larger precursors) and dissolution processes of podosomes in human macrophages (Kopp et al, 2006).…”
Section: Dynamics and Turnovermentioning
confidence: 99%
“…Accordingly, myosin II has been localized to podosomes in osteoclasts (Krits et al, 2002) and dendritic cells (van Helden et al, 2008), in which it surrounds the core structure. Conflicting data exist about the exact role of myosin (Burgstaller and Gimona, 2005;Clark et al, 2006;Kopp et al, 2006;Collin et al, 2008), but a possibly unifying hypothesis proposes that basal myosin-II activity is required for the formation and maintenance of podosomes, whereas sudden increases in myosin-II activity trigger podosome dissolution (van Helden et al, 2008). Myosin-generated contractility can, depending on substrate stiffness, also be translated into traction forces beneath podosomes, which would enable them to function as mechanosensors (Collin et al, 2008).…”
Section: Local Contractilitymentioning
confidence: 99%